PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA PENGGABUNGAN GAMBAR 2D KE DALAM SAJIAN MULTIMEDIA - Ni Made Ari Kamelia Dewi; Nyoman Sugihartini; Made Windu Antara Kesiman; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The aimed of  this study are (1) to describe and inform about aspects of what should be contained in the development of performance assessment instruments merging 2D image into a multimedia presentation, (2) obtain realistic results of a performance evaluation, (3) test the reliability rater performance appraisal instrument, (4) obtain information from teachers of vocational subjects on the practicality of competency assessment instruments merging performance 2D image into a multimedia presentation . This study tested the X Multimedia class second semester of the school year 2012/2013 at SMK N 3 Singaraja.  This research development of so-called popular or research and development. The development of these instruments through several stages of development curriculum analysis instruments that needs analysis SK / KD , preparation lattices and assessment rubrics, test content validity, validity and reliability of the grain problem, rater reliability and practicality. In doing this research trial involves two teachers as raters, who have competence in the standard competencies.  The results of this study are as follows. To validate the content level is calculated using the formula 1.00 Gregory and obtained results. This value is classified in the excellent category. Data obtained from the second phase of the validation is empirical test data. This data is then used to find the validity and reliability of the instrument was calculated using the formula instrumen.Validitas product moment correlation coefficient and the results showed that there were six items were invalid and valid thirty- two. As for reliability iinstrumen calculated  formula alpha Cronbach and obtain a yield of 0.81. Inter-rater reliability was also calculated in this study, is to involve two teachers as assessors. Inter- rater or rater reliability was calculated using the formula Ebel, known to yield at 0.80 while the practicality of the instrument is calculated using the theoretical ideal benchmark assessment, which is known from the calculation results of the practicality of the instrument at 32.05. This means that the performance assessment instrument has a very practical level qualification.